The Representation of Culture in “Bumi Manusia” Novel by Pramoedya Ananta Toer - Alemina Br. Perangin-angin; Widya Andayani; Reja Aprilla Brahmana; Mellya Miranda Putri; M. Sya’banul Khoir (Masyarakat Linguistik Indonesia Universitas Andalas, 2023)
Critical discourse analysis is a view of language in discourse analysis that views powers as always involved in forming subjects represented in language. The AWK model used in this paper is Norman Fairclough’s critical discourse analysis. Critical discourse analysis, which generally analyzes media texts, can also be used to analyze literary works, including novels. The novel analyzed by Norman Fairclough’s discourse analysis is the novel Bumi Manusia by Manusiaya Ananta Toer. Norman Fairclough’s discourse analysis examines text, discourse practice, and sociocultural practice. The three aspects of Norman Fairclough’s discourse analysis can be answered through the descriptive method text section the researcher can find three basic elements in the Norman Fairclough model, namely elements of representation, relations, and identity in the novel Bumi Manusia. Meanwhile, this paper will only discuss one element, namely representation. The result of this research is that culture is found in the text of the novel Bumi Manusia, in the form of daily behavior, language, clothes, to the names that appear in the text of the novel. In the text of the Bumi Manusia novel, there are also several cultures, not only Indonesian culture but, there is also Dutch culture by the contents of the story or synopsis of the novel describes indigenous life side by side with the Dutch.